TINJAUAN YURIDIS PEMIDANAAN CYBERCRIME DALAM PERPEKTIF HUKUM PIDANA POSITIF - Sri Sumarwani (Jurnal Pembaharuan Hukum, 2014)
Advances in technology have brought changes and rapid shifts in a life without limits. progress behind it, also has spawned new concerns-concerns with the advent of sophisticated crime in the form of Cybercrime. crime in the virtual world is an attempt to enter and or using a computer or computer network facility without a license and unlawfully with or without cause changes and or damage to computer facilities or used to enter it. Perpetrators of such crimes are not limited to age, territorially crime is also a cross-border crime. The research used in this journal using normative juridical approach, thats explains about the provisions of the legislation in force, associated with the reality on the ground, then analyzed by comparing the demands of ideal values that exist in the legislation with the reality on the ground. The results obtained indicate that the review of judicial punishment in positive criminal law in Indonesia comes in the Criminal Code and the Criminal Code in accordance with the arrangements beyond conventional crime.